Analisis Pengembangan Sistem Penyediaan Air Minum Berdasarkan Kajian Finansial dan Keterjangkauan Daya Beli Masyarakat (Studi Kasus: SPAM Pusat Kota Palangka Raya) - Massora, Reslisari Rara; Zevi, Yuniati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Palangka Raya, as the capital of Central Kalimantan Province, is facing an increasing demand for drinking water due to rapid population growth. PERUMDAM, as a regional government-owned company (BUMD) responsible for public services, plays a crucial role in providing safe drinking water to the community. To address this issue, the local government is planning to develop a piped drinking water supply system (SPAM) using water sources from the Tumbang Rungan intake. This study aims to analyze the financial feasibility of this development plan using indicators such as Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate Return (IRR), and Payback Period (PP), while also considering the affordability of the community through the Contingent Valuation Method (CVM). The evaluation results show that the willingness to pay (WTP) is IDR 11.872/m³ and the ability to pay (ATP) is IDR 7.084/m³, both of which are higher than the current tariff of IDR 4.780/m³. This indicates that the community is willing to accept a tariff increase for better services. The financial feasibility analysis shows that this project is viable and supports efforts to expand piped drinking water services in Palangka Raya.